Investigation of Antitumor and Antibacterial Properties of Some New Thiophene-2,5-Dicarboxylic Acid bis-aryl (alkyl) amide Compounds - Koparir, Pelin; Parlak, Akif Evren (My University, 2018)
Thiophene-derived compounds are of interest in chemistry, biology and pharmacology because of theirvarious pharmacological activities This study aims to investigate the antitumor and antibacterial activity ofthiophene-2,5-dicarboxylic acid bis-aryl (alkyl) amide compounds. In this study, the properties of antibacterialand antitumor were determined in vitro media, for all compounds.As a result, cell viability experiments show that some of this compounds have effective in vitro antitumoractivity. In addition, it has also been found that some compounds have an effective antibacterial activity.
Keywords: Mikrobiyoloji; Kimya; Tıbbi; Onkoloji; Biyokimya ve Moleküler Biyoloji